Dynamic Modeling of CO2 Transcritical Power Cycle for Waste Heat Recovery of Gasoline Engines. (May 2017) - Li, Xiaoya; Shu, Gequn; Tian, Hua; Shi, Lingfeng; Wang, Xuan
Abstract: Waste heat recovery by means of a CO2 transcritical power cycle (CTPC) is capable of dealing with high-temperature heat sources and achieving miniaturization, which has become attractive in thermal management of engines. In current work, a dynamic model of CTPC is presented together with the results of dynamic response and system sensitivity with respect to the external inputs. Results show that pump rotational speed and temperature of exhaust gas and cooling water greatly influence system performance indicated by net power output and thermal efficiency. While the influence of mass flow rate is less. Moreover, system is more sensitive when input parameters make the system condition severe. This preliminary research will be useful for future system-level design and control studies.